Evaluation of simple antioxidant blood parameters in patients with migraine - Yang, Zhenzhen; Xu, Pengfei; Geng, Chaofan; Zhang, Hongju (Frontiers in Neurology, 2022)
Background The study aims to investigate the role of serum albumin (ALB) and creatinine (CRE), bilirubin (BIL), and uric acid (UA) as major intravascular antioxidants in migraine. Methods We enrolled 148 patients with migraine and 150 age- and sex-matched healthy controls. The serum levels of ALB, TBIL, CRE, and UA were measured in patients with migraine of different subtypes. The risk of migraine was assessed by multiple stepwise logistic regression analysis. Results The serum levels of ALB, total BIL (TBIL), CRE, and UA were significantly lower in the migraine group than in the HC group (p < 0.05). The ALB and UA levels were lower during migraine attack periods (p < 0.05). There were no statistically significant differences observed in serum ALB, TBIL, CRE, and UA levels between aura/without aura and episodic/chronic migraine subtypes (p > 0.05). The multiple stepwise logistic regression revealed that ALB [odds ratio (OR) 0.79, 95% confidence interval (CI) 0.69–0.89, p < 0.001], TBIL (OR 0.61, 95% CI 0.5–0.75, p < 0.001), and UA (OR 0.97, 95% CI 0.96–0.99, p = 0.014) were independently associated with migraine. In addition, the serum levels of ALB, TBIL, and UA were significantly lower in the migraine group when compared by sex. Conclusion The serum levels of UA, TBIL, ALB, and CRE were lower in the patients with migraine, indicating a lower antioxidant status. In addition, ALB, TBIL, and UA were independently related to migraine. These results could provide insights into the possible role of oxidative stress in the pathogenesis of migraine.